(untitled) (Bangladesh Journal of Otorhinolaryngology, 2009)
This is a cross sectional study done in I.C.U & Dept. of otolaryngology - Head & Neck Surgery, B.S.M.M.U, Dhaka and Dhaka Medical College Hospital during the period of 1st March, 2003 to 30th August, 2003. 60 cases of tracheostomies, were included in this study, among them 30 cases of elective tracheostomies and 30 cases of emergency tracheostomies. In this study mean age of elective tracheostomy was 40.46 years & mean age of emergency tracheostomy was 50.50 years. Here Male was predominant both in elective (M:F= 6.5:1) and emergency tracheostomy (9:1). The common indications of elective tracheostomy were ICSOL (26.67%) & Head injury (26.67%) where as commonest indication of emergency tracheostomy was laryngeal carcinoma (53.33%). The frequency of complication for elective tracheostomy was 9.99% and emergency tracheostomy 33.35%. Here complications were 3.33 times more common in cases of emergency tracheostomy then elective tracheostomy. Key-words: Tracheostomy, elective and emergency. DOI: 10.3329/bjo.v14i2.3282 Bangladesh J of Otorhinolaryngology 2008; 14(2) : 57-62